(untitled) (Research, Society and Development, 2021)
Objective: To validate the six-minute step test (6MST) and evaluate its reproducibility for determining exercise tolerance in healthy children aged 7-11 years. Methods: 66 healthy children, aged between 7 and 11 years old, were included in the research. The volunteers underwent the six-minute walk test (6MWT) and the 6MST. Results: A moderate positive correlation was observed between the distance covered on the 6MWT and the number of climbs on the 6MST (r = 0.43; p <0.001). The reproducibility of the variables in the 6MST was considered excellent in relation to the variables Performance (number of steps) (r = 0.92; CI = 0.87 to 0.87; p <0.001), systolic blood pressure (SBP) immediately after (r = 0, 87; CI = 0.79 to 0.92; p <0.001), SBP-1 ’recovery (r = 0.84; CI = 0.74 to 0.90; p <0.001), maximum heart rate (HR) (r = 0 , 90; CI = 0.83 to 0.94; p <0.001), HR-immediately after (r = 0.88; CI = 0.81 to 0.93; p <0.001) and lower limb (LL) fatigue test (3rd min) (0.86; CI = 0.78 to 0.92; p <0.001). They also showed very good reproducibility at SBP-rest (r = 0.75; CI = 0.59 to 0.84; p <0.001), SBP-5 ’recovery (r = 0.78; CI = 0.56 at 0.83; p <0.001), diastolic blood pressure (PAD) rest (r = 0.74; CI = 0.58 to 0.84; p <0.001), DBP -immediately after (r = 0.72; CI = 0.55 at 0.83; p <0.001), DBP-1’recovery (r = 0.77; CI = 0.63 to 0.86; p <0.001), DBP-5’recovery (r = 0.73; CI = 0.56 to 0.83; p <0.001), HR-rest (r = 0.73; CI = 0.60 to 0.86; p <0.001), LL fatigue-immediately after (r = 0, 72; CI = 0.54 to 0.83; p <0.001). Conclusion: The 6MST is safe, valid and with good intra-rater reproducibility in the assessment of exercise tolerance in healthy children aged 7-11 years.